041 Psychosis: a rare manifestation of moyamoya disease in an adult. Issue 12 (14th November 2019) - Gupta, Srishti; Jaiswal, Amit; Sarkar, Srishti; Hosseini, Akram
Abstract : Introduction: Moyamoya disease is a chronic progressive cerebrovascular occlusive disease with prominent basal collateral vessels which appear hazy like a puff of smoke on angiography. Neuropsychiatric disorders have been reported in 20–60% cases and the most common manifestations include depression, anxiety and other cognitive disorders. However, only a few case reports of onset of a psychotic disorder following a cerebrovascular accident. We present a rare presentation of Moyamoya disease in adulthood. Case: A 44-year-old man from Bangladesh presented with acute psychotic episodes of visual, auditory and tactile hallucinations, paranoia, somatoform disorders and non-epileptic attacks. He had a 3-year history of mental health disorders and was later admitted to the hospital with a headache and hemiparesis secondary to an intraventricular haemorrhage. The neuroimaging showed characteristic appearances of Moyamoya disease. Neurosurgical multidisciplinary meeting discussion opted for conservative management and stroke rehabilitation. Despite the improvement of his neurological deficits, he continued to show apathy, depression, psychogenic attacks with features of executive dysfunction. Due to family history of juvenile death in the family, the patient had genetic testing and was found to have the mutation in the gene Ring finger protein 213 (RNF213). Conclusion: This case highlights the awareness of neuropsychiatric manifestation of Moyamoya disease that could be related to the interruption of the striato-thalamo-cortical circuits. The susceptibility to Moyamoya disease-2 (MYMY2) may be conferred by variation in the RNF213 gene on chromosome 17q25.